Parabolic Equation Modeling of Electromagnetic Wave Propagation over Rough Sea Surfaces - Ying Gao (Sensors, 2019)
The parabolic equation is an efficient numerical solution for electromagnetic wave propagation. In order to address the difficulties in predicting electromagnetic wave propagation in the maritime environment caused by atmospheric dust and rough sea surfaces, and the shortcomings of the existing research that cannot fully reflect the rough characteristics of sea surfaces, the authors have modelled electromagnetic wave propagation in the maritime environment, including in the presence of atmospheric dust. In this study the authors present a parabolic equation modeling method for calculating the electromagnetic wave propagation over rough sea surfaces. Firstly, the rough sea surface is generated by building a double summation model of three-dimensional random sea surface. Then, combined with the piecewise linear shift transformation method of the parabolic equation model, the parabolic equation random sea surface model is constructed, and the electromagnetic wave propagation characteristics in a rough sea environment are analyzed. Finally, a large number of results are compared with the Miler-Brown model and shadow effect model in rough sea environments, which verifies that the random sea surface model can better characterize the influence of rough sea surfaces on electromagnetic wave propagation. The model can be used to improve the reliability of marine microwave communication links and the detection performance of ship-borne radar.